Cardiorespiratory considerations for return-to-play in elite athletes after COVID-19 infection: a practical guide for sport and exercise medicine physicians. Issue 19 (2nd September 2020) - Wilson, Mathew G; Hull, James H; Rogers, John; Pollock, Noel; Dodd, Miranda; Haines, Jemma; Harris, Sally; Loosemore, Mike; Malhotra, Aneil; Pieles, Guido; Shah, Anand; Taylor, Lesley; et al.
Abstract : SARS-CoV-2 is the causative virus responsible for the COVID-19 pandemic. This pandemic has necessitated that all professional and elite sport is either suspended, postponed or cancelled altogether to minimise the risk of viral spread. As infection rates drop and quarantine restrictions are lifted, the question how athletes can safely resume competitive sport is being asked. Given the rapidly evolving knowledge base about the virus and changing governmental and public health recommendations, a precise answer to this question is fraught with complexity and nuance. Without robust data to inform policy, return-to-play (RTP) decisions are especially difficult for elite athletes on the suspicion that the COVID-19 virus could result in significant cardiorespiratory compromise in a minority of afflicted athletes. There are now consistent reports of athletes reporting persistent and residual symptoms many weeks to months after initial COVID-19 infection. These symptoms include cough, tachycardia and extreme fatigue. To support safe RTP, we provide sport and exercise medicine physicians with practical recommendations on how to exclude cardiorespiratory complications of COVID-19 in elite athletes who place high demand on their cardiorespiratory system. As new evidence emerges, guidance for a safe RTP should be updated.